Deformed Schioberg-Type Potential and Rotational-Vibrational Spectra for Some Diatomic Molecules - Hama, Fakhir Omer (Eastern Mediterranean University EMU, 2017)
This thesis aims to discuss the deformed Schiӧberg-type potential for some diatomic molecules. The s conditions are used to show a common diatomic molecular potential model. It also aims to employ the radial spherically symmetric Schrӧdinger equation and convert our potential into a format that allows us to use supersymmetric quantization and find a closed form analytical solution for the rotational and vibrational energy levels. We talk about our findings by utilizing three diatomic molecules ( ), HF ( ) and ( ). The findings of the thesis showed that there is a great comparison with those from a generalized pseudospectral numerical method (GPS). Keywords: rotational-vibrational energy spectra, deformed Schiӧberg-type potential, diatomic molecules. .

ÖZ: Bu tezin amacı iki-atomlu moleküllerde deforme edilmiş Schiöberg-tipi potansiyellerin incelenmesidir. Ortak iki-atomlu molekül potansiyelinin tesbitinde Varshni şartları kullanılmıştır. Ayrıca radyal simetrik Schrödinger denklemi potansiyeli supersimetrik Kuantum formatına sokulup dönme ve titreşimli enerji seviyeleri tam olarak bulunmuştur. Üç örnek seçilmiştir, bunlar H2(x1Σ , HF(x1Σ ve N2(x1Σ ‘dır. Tezin bulguları genelleştirilmiş spektral gibi görünen nümerik yöntemlerle mukayese edilebildiğini göstermiştir. Anahtar sözcükler: dönmeli – titreşimsel enerji spektrumu, deforme edilmiş Schiöberg-tipi potansiyel, iki-atomlu moleküller.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2017. Supervisor: Prof. Dr. Omar Mustafa.
Keywords: Molecular Physics; rotational-vibrational energy spectra; deformed Schiӧberg-type potential; diatomic molecules; Physics